Upaya Meningkatkan Hasil Belajar Peserta Didik dengan Menerapkan Model Pembelajaran Problem Based Learning Berbantuan Metode Mind Mapping Mata Pelajaran Pendidikan Agama Katolik dan Budi Pekerti Kelas XI di Sma Negeri 3 Yogyakarta - Iin Danis Ariyani; Andarweni Astuti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to improve students' learning outcomes by implementing the Problem Based Learning (PBL) model supported by the Mind Mapping method in the Catholic Religious Education and Character Education subject for class XI students at SMA Negeri 3 Yogyakarta. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observation sheets of learning implementation and questionnaires to assess students' learning outcomes. The results of the learning implementation observation showed significant improvement, from 57.8% in cycle 1 to 64.7% in cycle 2. Furthermore, the average score of students' learning outcomes in the daily assessment of the Church and World material increased from 80 in the pre-cycle, to 87.27 in cycle 1, and 90.98 in cycle 2. Students' responses to the use of this method also showed an increase in satisfaction, with 97% in cycle 1 and 100% in cycle 2. Based on these findings, it can be concluded that the implementation of the PBL model supported by the Mind Mapping method is effective in improving students' learning outcomes and enhancing students' interest and satisfaction in the learning process.